(3JfVjQ GdYbhO GdSfjI HJegjO GdOhdI GdMSfjIs - (3GdehShj , QVj GdOjf Hf eMeO Hf Ydj Hf MjOQ Hf Ydj GdehShj,J (B1168 (3g` s
(3ChdgG (B:s
(3hHYO Efi deG QCjJ Yde GdJGQjN ef CLd GdYdhe ebOQkG aMjfFP ShdJ di faSi HCf CaQZ ai HjGV GdeWQhS faSi s
(3BNQgG (B:s
(3hde jYbH ef GdPchQ EdG hdOkG GSeg jMji , fQLh Cf jYjT Hg GSe hGdOg hjMjG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B167s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B126 s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI GdMceI HHZOGO (B(138) s
Keywords: (3GdJGQjNs